Optimal In-Stream Structure Design through Considering Nitrogen Removal in Hyporheic Zone - Suning Liu (Water, 2020)
The hyporheic zone (HZ), the region beneath or alongside a streambed, can play a vital role in a stream ecosystem. Previous studies have examined the impacts of in-stream structures on the HZ and river restoration; however, studies on optimizing the design of in-stream structures are still lacking. Therefore, this study aims to propose a method for optimizing the design of in-stream structures (e.g., weirs) through comprehensively considering both nitrogen removal amount (NRA) and nitrogen removal ratio (NRR) in the HZ based on numerical modelling. The Hydrologic Engineering Center’s River Analysis System (HEC-RAS) and COMSOL Multiphysics are employed for surface water and hyporheic flow simulations, respectively, and these two models are coupled by the hydraulic head along the surface of the streambed. The NRA and NRR are both closely related with residence time (RT), while the NRA is also influenced by hyporheic flux. Using the model outputs under different scenarios, regression equations for estimating the relevant variables (e.g., the maximum upstream distance in the subsurface flow influenced by the weir, the RT, and the hyporheic flux) are proposed. Then, the cumulative NRA (CNRA) and NRR can be calculated, and an objective function is formulated as the product of the normalized CNRA and NRR. The results show that the optimal height of the weir can be obtained based on the proposed method, and the validation shows the good general performance of this method. Sensitivity analysis indicates that the optimal height generally can be sensitive to the river discharge, i.e., the optimal height increases when the river discharge increases and vice versa. In addition, it is observed that, in the case of the optimal height, hyporheic flux increases when the slope increases while the influence of depth to bedrock on hyporheic flux is not significant. This study enhances our understanding of the optimal in-stream structure design, and potentially benefits river restoration in the face of continual degradation caused by human activities.